Meningkatkan Hasil Belajar Siswa dengan Model Pembelajaran Picture And Picture Kelas V SDN 4 Sukoharjo - Aryanto, Eko (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
In class V learning at SDN 4 Sukoharjo, Tirtomoyo District in 2020/2021, student learning outcomes are low. Of the 13 students, only 4 students (31%) completed with an average grade of 62.46 even though the KKM score was 70. The purpose of this study is to improve student learning outcomes by applying the Picture and Picture learning model. The research was carried out in 2 cycles, cycle 1 on October 27, 2020 and cycle 2 on November 3, 2020. The results of improving learning using the Picture and Picture learning model are quite significant, in the first cycle students who complete are 8 students (62%) with a class average of 73.23 and in the second cycle students who complete increase to 13 students (100%) with the average value of the class increased to 88.92. From these results, it can be concluded that the application of the Picture And Picture learning model can improve the learning outcomes of the fifth grade students of SDN 4 Sukoharjo Semester 1 of the 2020/2021 Academic Year.